The DNA-Based Authentication of Commercial Herbal Products Reveals Their Globally Widespread Adulteration - Ichim, Mihael Cristin (Frontiers in Pharmacology, 2019)
The herbal products, sold worldwide as medicines or foods, are perceived as low risk because they are considered natural and thus safe. The quality of these products is ineffectively regulated and controlled. The growing evidence for their lack of authenticity is causing deep concern, but the scale of this phenomenon at global, continental or national scale remains unknown. We analyzed data reporting the authenticity, as detected with DNA-based methods, of 5,957 commercial herbal products sold in 37 countries, distributed on all inhabited continents. Our global survey shows that a substantial proportion (27%) of the herbal products commercialized in the global marketplace is adulterated when their content was tested against their labeled, claimed ingredient species. The adulterated herbal products are distributed across all continents and regions. Our results confirm the large-scale presence of adulterated herbal products throughout the market. The adulterated herbal products contain undeclared contaminant, substitute, and filler species, or none of the labeled species, which all may be accidental or intentional, economically-motivated and fraudulent. The globally widespread adulteration is a serious threat to consumers’ well-being and safety, in spite of herbal products’ claimed or expected health benefits.